Angiopoietin-2 in chronic renal failure patients on hemodialysis: Relationship with glomerular filtration rate in the predialysis stages - Fatma A Attia; Nagwa A Mohammed; Al-Shymaa A Ibrahim (SpringerOpen, 2013)
Introduction Cardiovascular disease has increased as a complication of chronic kidney disease even in the absence of diabetes or hypertension. Angiopoietin-1 and 2 are 55 kDa antagonistic nonredundant gatekeepers of endothelial activation and thus are potential important factors in accelerated atherosclerosis. Aim of the study The aim of the study was to determine angiopoietin-2 level in patients on hemodialysis (stage 5) and in the predialytic stages (stages 3 and 4) and to find the relationship between angiopoietin-2 levels and glomerular filtration rate in the predialytic stages. Patient and methods We prospectively studied 75 patients divided into three groups and 12 healthy controls. Group 1 included 33 patients on maintenance hemodialysis three times a week; group 2 included 21 patients with stage 3 chronic kidney disease; and group 3 included 21 patients with stage 4 chronic kidney disease. Results We found highly significant (P < 0.01) increase in mean serum angiopoietin-2 levels in all three groups compared with the control. The mean angiopoietin-2 in group 1 was 1669.09 ± 472.64 pg/ml, in group 2 was 1206.91 ± 154.26 pg/ml, in group 3 was 1642.24 ± 113.01 pg/ml, and in control was 476.29 ± 150.37 pg/ml. Furthermore, we found highly significant (P < 0.01) increase in group 1 compared with group 2 and group 3, and in group 3 compared with group 2. Our result revealed significant negative correlation of angiopoietin-2 level with estimated glomerular filtration rate in group 2 (r - 0.858, P < 0.01) and group 3 (r - 0.825, P < 0.01), with hemoglobin in group 1 (r - 0.438, P < 0.01), and with BMI (r − 0.468, P < 0.05) and cholesterol (r − 0.503, P<0.05) in group 3; significant positive correlation was observed with uric acid (r 0.456, P < 0.05) in group 3. Conclusion Circulating angiopoietin-2 is a putative marker and potential mediator of atherosclerosis, is inversely related to glomerular filtration rate, and is increased with advanced chronic kidney disease. Normolipidemia in chronic kidney disease patients does not prevent atherosclerotic burden; this is because of the presence of other markers such as angiopoietin-2.